ANTARA BEZITSRECHT DAN EIGENDOMRECHT: Kajian Tentang Hak Atas Tanah Oleh Penduduk - Juwono, Harto (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
Nowadays, land ownership's issues become complicated and often result in conflict to nation, either individually or groups (mass). Lack of clarity of the status of the land requires a historical approach to the study of the legal regulation of land that changed following regime, which resulted in changes to the rights and status of land ownership. Results of this study concluded that the problems came out from an incomprehensive notice from the regulator/government, in order to clarify which regime used by now. Most of the people are sticking with the understanding of property rights (bezitzrecht) or tenure (beschikkingsrecht) of land, which is different from the concept of land title rights (eigendom). Therefore, the Government is expected to socialize the concept of land title rights (eigendom) and other present land rights so the conflicts will decrease or subside. Keyword: property rights (bezitzrecht), land title rights (eigendom), regulation history